2020
DOI: 10.1111/febs.15348
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of human guanylate‐binding protein 1 coupled to the release of structural restraints imposed by the C‐terminal domain

Abstract: Human guanylate-binding protein 1 (hGBP-1) shows a dimer-induced acceleration of the GTPase activity yielding GDP as well as GMP. While the head-to-head dimerization of the large GTPase (LG) domain is well understood, the role of the rest of the protein, particularly of the GTPase effector domain (GED), in dimerization and GTP hydrolysis is still obscure. In this study, with truncations and point mutations on hGBP-1 and by means of biochemical and biophysical methods, we demonstrate that the intramolecular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Extensive structural and biochemical studies of non-farnesylated GBP1 revealed how GBP1 catalyzes the hydrolysis of GTP in two consecutive steps to GDP and GMP [18,19,[34][35][36][37][38][39][40][41][42][43] (Figure 1A -B). Initial GTP binding by monomeric GBP1 is mediated by the consensus nucleotide binding motifs (G1-4) of its nucleotide binding pocket.…”
Section: Structure and Gtpase Activity Of Gbp1mentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive structural and biochemical studies of non-farnesylated GBP1 revealed how GBP1 catalyzes the hydrolysis of GTP in two consecutive steps to GDP and GMP [18,19,[34][35][36][37][38][39][40][41][42][43] (Figure 1A -B). Initial GTP binding by monomeric GBP1 is mediated by the consensus nucleotide binding motifs (G1-4) of its nucleotide binding pocket.…”
Section: Structure and Gtpase Activity Of Gbp1mentioning
confidence: 99%
“…LG:LG interface between two GBP1 molecules resulting in a head-to-head dimer which is in a rapid equilibrium with GTP-bound monomers [36,41,43].…”
Section: Structure and Gtpase Activity Of Gbp1mentioning
confidence: 99%
See 3 more Smart Citations